Exhibition Review. (1st March 2019) - Sklar, Monica
Too Fast to Live, Too Young to Die: Punk Graphics, 1976–1986 Exhibition and Shepard Fairey: Salad Days, 1989–1999 Exhibition, Andrew Blauvelt, Steffi Duarte and Andrew Krivine, Cranbrook Art Museum, Bloomfield Hills, MI, 16 June–7 October 2018